2003
DOI: 10.1590/s0103-97332003000300013
|View full text |Cite
|
Sign up to set email alerts
|

Lattice models of disorder with order

Abstract: This paper describes the use of simple lattice models for studying the properties of structurally disordered systems like glasses and granulates. The models considered have crystalline states as ground states, finite connectivity, and are not subject to constrained evolution rules. After a short review of some of these models, the paper discusses how two particularly simple kinds of models, the Potts model and the exclusion models, evolve after a quench at low temperature to glassy states rather than to crysta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…This continuous evolution stops because the system gets trapped in a disordered state and escape from this state is slow because the process is thermally activated [21]. When the final temperature is zero, it was noticed previously that the ground state may not be reached [22,23]. It was further suggested that for q ≥ d + 1, glassy evolution can occur [20,21,24,25] because the system gets pinned in a disordered state and the ultimate relaxation to equilibrium proceeds via thermally activated processes [20,21], [26]- [28].…”
Section: Introductionmentioning
confidence: 98%
“…This continuous evolution stops because the system gets trapped in a disordered state and escape from this state is slow because the process is thermally activated [21]. When the final temperature is zero, it was noticed previously that the ground state may not be reached [22,23]. It was further suggested that for q ≥ d + 1, glassy evolution can occur [20,21,24,25] because the system gets pinned in a disordered state and the ultimate relaxation to equilibrium proceeds via thermally activated processes [20,21], [26]- [28].…”
Section: Introductionmentioning
confidence: 98%